2017
DOI: 10.1002/adsc.201701105
|View full text |Cite
|
Sign up to set email alerts
|

Directed C–H Alkenylation of Aryl Imines with Alkenyl Phosphates Promoted by a Cobalt–N‐Heterocyclic Carbene Catalyst

Abstract: We report herein an ortho-C-H alkenylation reactiono fa ryl imines with alkenyl phosphates promoted by ac obalt-N-heterocyclic carbene (NHC)c atalytic system. While commercially available bulky NHC ligands exhibited only modest catalytic activity,e laborationo ft he nitrogen substituents and backbone of the NHC enabled the desired transformation to proceed in high yield at am ild temper-ature.T he newC o-NHC system proveda pplicable to av ariety of aryl iminesa nd alkenyl phosphates to afford ortho-alkenylated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 107 publications
(29 reference statements)
1
15
0
Order By: Relevance
“…By contrast, imines bearing m -methoxy, m -fluoro, or a 3,4-methylenedioxy group underwent exclusive alkenylation at the proximity of the functional group to afford the products 3ia – ka in good yields. As was also observed in previously reported cobalt-catalyzed ortho C–H functionalization reactions [ 22 23 28 29 ], this regioselectivity may be ascribed to the role of the oxygen or fluorine atom as a secondary directing group to have an electrostatic interaction with the cobalt center during the C–H activation. For compound 3ja , an increased acidity of the ortho position of the fluorine atom could have also contributed to the observed regioselectivity [ 31 ].…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…By contrast, imines bearing m -methoxy, m -fluoro, or a 3,4-methylenedioxy group underwent exclusive alkenylation at the proximity of the functional group to afford the products 3ia – ka in good yields. As was also observed in previously reported cobalt-catalyzed ortho C–H functionalization reactions [ 22 23 28 29 ], this regioselectivity may be ascribed to the role of the oxygen or fluorine atom as a secondary directing group to have an electrostatic interaction with the cobalt center during the C–H activation. For compound 3ja , an increased acidity of the ortho position of the fluorine atom could have also contributed to the observed regioselectivity [ 31 ].…”
Section: Resultssupporting
confidence: 80%
“…No significant improvement was observed using the saturated analogues of IMes·HCl and IPr·HCl ( Table 1 , entries 5 and 6) or the 2,6-diethylphenyl analogue (IEt·HCl, Table 1 , entry 7). Furthermore, the NHC precursor featuring a cyclohexane backbone and 2,6-diethylphenyl groups ( L1 ·HBr), which proved to be the optimal ligand for the C–H arylation of pivalophenone N–H imine as well as for the C–H alkenylation of N-arylimine ( Scheme 1 , b) [ 28 29 ], was not particularly effective for the present reaction ( Table 1 , entry 8). To our delight, we observed a remarkable improvement in the reaction efficiency using the benzofused analogue of IPr·HCl ( L2 ·HCl), affording 3aa in 88% yield without any trace of a dialkenylation product ( Table 1 , entry 9).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[80][81][82][83][84][85][86][87] Cobalt-promoted monoalkenylation of naphthyl imines using alkenyl phosphates has been described recently by Yoshikai. 88 The procedure is well adapted for the installation of cyclic alkenes (Scheme 22). It has been shown that elaboration of NHC ligands and fine-tuning of the nitrogen substituents as well as the backbone of the NHC was beneficial to the alkenylation process compared with more classical and commercially available NHC ligands.…”
Section: Scheme 19 24-substitution Pattern Through Catellani's Methomentioning
confidence: 99%